The historical avulsion of the Tista River, and its relationship to the Brahmaputra: Map and archive evidence from 1750 to 1835. Issue 3 (22nd June 2021) - Richards, Keith; Brammer, Hugh; L. Saunders, Patricia
Abstract : Alluvial fans are constructed when river deposition raises local elevations until the river "avulses" to an alternative lower elevation alignment. Avulsions may be triggered by exogenous events, such as floods that locally overtop the river's banks; they may then cause extreme flooding on a fan and have major impacts. Rivers draining the Himalayas into the Gangetic plain have behaved historically in this way; for example, the Kosi River's historical westward migration (1731–1963), and its recent eastward shift (1980). In the major fan‐delta of the Bengal Basin, the Brahmaputra and its tributary, the Tista, have both undergone historical avulsions, with some suggestion that these may have been causally linked. Between the Rennell survey of Bengal (1765–77) and the partial re‐survey by Wilcox and Ommanney (1828–35), the Brahmaputra River substantially changed its course. In Rennell's time it turned south‐east into the Sylhet Basin leaving the higher land of the Madhupur Tract on its right; by 1830, it flowed due south with the Tract on its left. One hypothesis for the timing and cause of this avulsion relates it to the impact of a major flood and avulsion in the River Tista in 1787. This paper examines the evidence of the Rennell maps, the East India Company archives of correspondence between District Collectors about flooding and avulsion in the Tista, and the diaries of Francis Hamilton Buchanan who travelled along the Tista in 1807–11. From these contemporary sources it is possible to re‐construct the changes in the River Tista in the late 18th century, and to conclude that its avulsion had little direct influence on that of the Brahmaputra, although it went through some radical rearrangements of its own. Abstract : The River Tista in Bengal experienced a major avulsion and a radical rearrangement of its course across its alluvial fan in 1787. This paper examines the evidence of the maps of James Rennell; the East India Company archives of correspondence between District Collectors about the consequential flooding in the Tista; and the diaries of Francis Hamilton Buchanan who travelled along the Tista in 1807–11. This combination of historical evidence enables reconstruction of the 1787 event, its causes and impacts; but also enables refutation of the hypothesis that the Tista may have been an influence on an even more radical change in the course of the Brahmaputra River a little later.